Zmiany demograficzne a polski rynek pracy - Zajączkowski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The thesis given at the beginning of the paper, that the ongoing changes in the demographic structure of Polish society have a crucial correlation with the labor market in Poland and in the near future will significantly affect its shape, causing a number of adverse effects for the country’s economy, was supported by the analysis of statistical data derived from the sources of Central Statistical Office of Poland. The conclusions obtained in such way largely confirm the claim raised at the beginning of the article. Furthermore, to verify the thesis expressed at the beginning of the article, there were analyzed the results of chosen reports coming from non-governmental sources, concerning opinion of employees over 50 and also their employers about their current situation on labor market. The sources analysis was based on the theoretical assumptions derived from selected literature, which were mentioned in the article’s beginning and partly in its main part. To confirm those conclusions derived from the analysis of statistical data they were confronted with abovementioned theoretical assumptions, which allowed for their critical analysis, as well as their proper evaluation.It should be noted that the processes ongoing in the Polish population, as indicated in the text of the report, the consequences of which have a negative impact on the Polish labor market, show mutual interdependence, making it necessary to develop multi-faceted solutions aimed at elimination of their effects. As one of the most important demographic phenomena occurring in this area one should point at the aging population and intensifying emigration of Poles. These problems, whose consequences will affect in the coming years the rate of growth of Polish economy and situation of public finances, require increased interest of institutions shaping Poland’s economic and social policy. Therefore, it is worth noting that some of the government agencies have already become engaged in efforts to cope with the abovementioned difficulties, however, these efforts should be intensified in the upcoming years, as the negative consequences associated with demographic processes occuring in Poland, will influence Polish society in the future with all of their severity, if they are left without counteraction.
Keywords: współczynnik zależności demograficznej; demografia; emigracja; rynek pracy; produktywność pracy; Polska; Polacy; wiek produkcyjny / postprodukcyjny; polityka socjalna; starzenie się społeczeństwa